Evaluation of Bending and Impact Strength Characteristics on Friction Stir Welding of Dissimilar 7075T651 – 6061T651 Butt Joints - Muruganandam, D.; Sushil Lal Das (Asian Review of Mechanical Engineering, 2012)
Aluminium alloys have gathered wide acceptance in the fabrication of light weight structures requiring a high strength-to weight ratio and good corrosion resistance. Modern structural concepts demand reductions in both the weight as well as the cost of the production and fabrication of materials. Therefore welding processes have proven more attractive, and there is an urgency to study their potential. Compared to the fusion welding processes that are routinely used for joining structural aluminium alloys, Friction Stir Welding (FSW) process is an emerging solid state joining process was invented in 1991 by TWI, in which the material that is being welded does not melt and recast. The major advantage in FSW process is that the maximum temperature reached is less than 80% of the Melting Temperature (TM), i.e., the joint is performed in the solid-state and excessive micro structural degradation of the weld zone is avoided. This process uses a non-consumable tool to generate frictional heat in the abutting surfaces. The welding parameters such as tool rotational speed, welding speed, axial force etc., and tool pin profile play a major role in deciding the joint strength. This paper focus on impact and bending strength evaluation and predicting the process parameters in varying rotational and welding speeds of friction-stir welding for the dissimilar precipitation hardenable aluminium alloys ie., between 6xxx (Al-Mg-Si) and 7xxx (Al-Zn-Mg).